3x-5(2x-5)=4(4-5x)+3

Simple and best practice solution for 3x-5(2x-5)=4(4-5x)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-5(2x-5)=4(4-5x)+3 equation:



3x-5(2x-5)=4(4-5x)+3
We move all terms to the left:
3x-5(2x-5)-(4(4-5x)+3)=0
We add all the numbers together, and all the variables
3x-5(2x-5)-(4(-5x+4)+3)=0
We multiply parentheses
3x-10x-(4(-5x+4)+3)+25=0
We calculate terms in parentheses: -(4(-5x+4)+3), so:
4(-5x+4)+3
We multiply parentheses
-20x+16+3
We add all the numbers together, and all the variables
-20x+19
Back to the equation:
-(-20x+19)
We add all the numbers together, and all the variables
-7x-(-20x+19)+25=0
We get rid of parentheses
-7x+20x-19+25=0
We add all the numbers together, and all the variables
13x+6=0
We move all terms containing x to the left, all other terms to the right
13x=-6
x=-6/13
x=-6/13

See similar equations:

| 7x+20=60-12x | | 1/8a=-5 | | 4(2a)=40 | | 400x+37=622 | | 11x+2=2(2×+4)+7×-6 | | -4=n+5.1-1.1 | | 37x+400=622 | | 8k+6=-10+6k | | -7(9x-3)=-483 | | 5(5a-5)-2=48 | | 91=5y+11 | | 4h+10=-3h-6+2 | | (n-2)*180=162 | | -104=6-10(2-x) | | 6+8p=6p-10 | | 3x+11=3x−19 | | 7x-58=180 | | -4(-5r+7)=-228 | | 2x+25=7x-15 | | 1=3q-q | | 0=4x-133x+5-x=2x+7 | | -4f+8=-6f-8 | | x-13=62/100 | | n+9=-9-5n | | 4x+32=4x+8 | | 2x+24=3x+5+40 | | 3.2=-0.8p | | 14-9y=5 | | 9y+9=10y | | 5(2x-2)=8x-3x+1 | | x+20=460 | | 7x+3(4x-8)-4=109 |

Equations solver categories